Competence Of Expertise, Experience, Auditor Professional Skepticism, And Audit Situation To The Relevance Of Providing Audit Opinion On an Entity's Financial Statements - RIYADI, Padlah; NUR, Erllycha Novian (PT Keberlanjutan Strategis Indonesia, 2023)
This research examines and provides empirical evidence that the factor of expertise, experience, professional skepticism of auditors and audit situations has no effect or relevance to the provision of audit opinion on the entity's financial statements. This research was conducted using the sampling method, namely purposive sampling, with the type of quantitative research. The data were analyzed using multiple regression analysis models. Hypothesis testing is done to determine the extent of expertise, experience, and professional skepticism of auditors and audit situations that affect the relevance of audit opinion on the financial statements of entities either partially or simultaneously. Hypothesis testing is done to determine the extent of expertise, experience, and professional skepticism of auditors and audit situations that affect the relevance of audit opinion on the financial statements of entities either partially or simultaneously.